(untitled) (Herald of Journalism, 2020)
The author considers the peculiarities of PR in the banking system, which in any way affect the economy of the state. Based on the works of foreign authors who have investigated the PR services in commercial organizations, offers ways to develop the image of the bank, building an effective public relations and opinion research. Describes in detail the im portant functions of PR, to ensure the success of the bank, such as media relations, expanding customer base, the relationships in the team of the bank, the protection of the bank’s image during the crisis.